Warehouse Receipt Guarantee Fund As Protection For Holders Or Recipients Of Warehouse Receipt Guarantee Rights - Nabila, Syadzwina Hindun (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: The agricultural sector is the backbone of the Indonesian economy. However, farmers still face various challenges, including limited access to finance, fluctuating commodity prices, and the dominance of middlemen in the supply chain. These conditions hinder the improvement of farmers' productivity and welfare. The warehouse receipt system works by providing farmers with proof of ownership of their crops in the form of warehouse receipts that can be used as collateral to obtain loans from financial institutions, giving farmers flexibility in selling their crops. However, the warehouse receipt system still faces a number of challenges, including the risk of loss due to failure of the warehouse manager. To address this, the government has established the Warehouse Receipt Guarantee Corporation, which aims to protect farmers' rights and increase confidence in the system.Purposes of the Research:  The purpose of this study is to examine how the warehouse receipt guarantee institution as a protection for warehouse receipt holders or recipients of collateral rights on warehouse receipts.Methods of the Research: This research is conducted in normative juridical, using literature data as secondary data to examine the rules and norms in law.Findings of the Research: The warehouse receipt guarantee institution provides protection and legal certainty to warehouse receipt holders and recipients of collateral rights from the failure of warehouse managers to carry out their duties which can result in physical damage to goods due to external factors such as natural disasters or internal factors such as negligence. This Warehouse Receipt Guarantee Agency will function as a guarantor like insurance if there are Warehouse Managers who experience bankruptcy. To protect the rights of warehouse receipt holders, Law Number 9 Year 2011 authorizes the Guarantee Institution to take action if the warehouse manager fails to perform his duties. The Guarantee Institution is authorized to make policies, handle problems, and even file for bankruptcy if necessary.